Nutritional inadequacies in commercial vegan foods for dogs and cats. - Rafael Vessecchi Amorim Zafalon; Larissa Wünsche Risolia; Thiago Henrique Annibale Vendramini; Roberta Bueno Ayres Rodrigues; Vivian Pedrinelli; Fabio Alves Teixeira; Mariana Fragoso Rentas; Mariana Pamplona Perini; Isabella Corsato Alvarenga; Marcio Antonio Brunetto (PLoS ONE, 2020)
The objective of this study was to evaluate the macronutrients composition, fatty acid and amino acid profiles, and essential minerals content of all vegan foods for dogs and cats available in the Brazilian market, and to compare results with FEDIAF (2019) and AAFCO (2019) recommendations. Four vegan pet foods were assessed (three for dogs and one for cats). The comparisons were made in a descriptive manner. All foods met the minimum recommendations for macronutrients. Arachidonic acid was not reported in any food label. Regarding the FEDIAF recommendations, one food for dogs had low calcium, another had low potassium and a third had low sodium. The cat food presented potassium content lower than recommended. The Ca:P ratio did not meet the minimum recommendation of FEDIAF (2019) and AAFCO (2019) in any of the dog's foods analyzed, and the cat food also did not present the minimum recommendation based on FEDIAF (2019). Copper concentrations exceeded the legal limit in all foods. Zinc concentrations exceeded this limit in two foods (one for dogs and one for cats) and iron levels exceeded the legal limit in one dog food. One of the dog foods did not meet the minimum recommendation for methionine and the cat food did not meet the minimum recommendation for arginine. In addition, when the amount of nutrients consumed by animals with low energy requirements was simulated, in addition to the same non-conformities described above, it was observed that the cat food does not meet the minimum recommended of protein and taurine in unit/Kg0.67. It was concluded that all foods analyzed had one or more nutrients below the recommended levels and some presented zinc and copper excess, therefore, these foods should not be recommended for dogs and cats, because dietary deficiencies found may lead to health risks for dogs and cats. Furthermore, manufacturers should review their formulations to ensure the nutritional adequacy of these foods.